Răspuns :
0,7 × ( 2,1 × 2 ÷ 3,5 + 5,6 ) - 0,004 =
= 0,7 × ( 4,2 ÷ 3,5 + 5,6 ) -0,004 =
= 0,7 x ( 1,2 + 5,6 ) - 0,004 =
= 0,7 x 6,8 - 0,004= =
= 4,76 - 0,004 =
= 4,756
= 0,7 × ( 4,2 ÷ 3,5 + 5,6 ) -0,004 =
= 0,7 x ( 1,2 + 5,6 ) - 0,004 =
= 0,7 x 6,8 - 0,004= =
= 4,76 - 0,004 =
= 4,756
0,7 x [ ( 3,4 - 1,3 ) x 2 : 3,5 + 0,7 x 8 ] - 0,008 : 2 =
= 0,7 x [ 2,1 x 2 : 3,5 + 5,6 ] - 0,004
= 0,7 x [ 4,2 : 3,5 + 5,6 ] - 0,004
= 0,7 x [ 1,2 + 5,6 ] - 0,004
= 0,7 x 6,8 - 0,004
= 4,76 - 0,004
= 4,756
= 0,7 x [ 2,1 x 2 : 3,5 + 5,6 ] - 0,004
= 0,7 x [ 4,2 : 3,5 + 5,6 ] - 0,004
= 0,7 x [ 1,2 + 5,6 ] - 0,004
= 0,7 x 6,8 - 0,004
= 4,76 - 0,004
= 4,756